ARGUMENTATIVE ESSAY COMPONENTS: A STUDY OF ENGLISH STUDENTS' WRITING AT UIN MAHMUD YUNUS BATUSANGKAR - Elfi (Universitas Mahaputra Muhammad Yamin, 2024)
Many students got problems in writing argumentative specially in apllying to write the component of essay such as attention getter, thesis statement, pro argument, counter argument, rebuttal, and conclusion. The purpose of this research is to find out how fourth semester English students of UIN Mahmud Yunus Batusangkar applying to write the component of argumentative writing in their essay. This research used a document analysis method. The object of this research was the argumentative writing components contained in the writings made by fourth semester English Department students of UIN Mahmud Yunus Batusangkar Academic Year 2022/2023. In this research, the researcher acts as a key instrument and the mid-semester IV exam documents. To test the validity of the data, researcher used source triangulation techniques. Furthermore, in analyzing the data includes data reduction, data presentation, and conclusion drawing which is the theory of Miles and Huberman (1994: 10-11). The finding showed that 45 students have applied to write the attention getter, thesis statement, and pro argument. 29 students have applied counter-arguments component, 13 students have applied to write rebuttal component, and 45 students have applied to write conclusion component. From the finding, writing rebuttal, counter argument and conclusion should be improve by the students in writing argumentative essay.